Development of the rural small manufacturing sector in Gujarat and West Bengal: a comparative study. Issue 2 (17th February 2020) - Dutta, Subrata
ABSTRACT: Rural, small, unorganised, manufacturing enterprises have received relatively less attention in the existing literature. This article examines issues related to the development of rural small manufacturing sector in Gujarat (known for emphasising industrialisation) and West Bengal (known for emphasising land reform and decentralisation of power). It finds that West Bengal has a huge number of rural own account manufacturing enterprises (OAME) compared to urban, whereas the rural-urban differential is not as significant in Gujarat. In West Bengal, the presence of large number of rural small manufacturing enterprises over urban counterparts suggests that much of the rural labour force has been trying to find income-earning opportunities outside agriculture.